Definitions of determinants of physical activity behaviour: process and outcome of consensus from the DE-PASS expert group - Jan Dygrýn; Javier Brazo-Sayavera; Joana Cruz; Mekdes Kebede Gebremariam; José Carlos Ribeiro; Laura Capranica; Ciaran MacDonncha; Yael Netz (International Journal of Behavioral Nutrition and Physical Activity)
Abstract Background Despite extensive research on physical activity behaviour (PAB), consensus is lacking on related terms and definitions, thereby hindering the ability to compare findings between studies and to develop reliable assessment tools. This study therefore aimed to establish consensus on the definitions of key PAB determinants. Methods First, an international expert steering committee was established, comprising members of the European Cooperation in Science and Technology (COST) action “DEterminants of Physical ActivitieS in Settings” (DE-PASS). Recently published review-level studies were used to identify key determinants of PAB. Two independent reviewers systematically reviewed the literature to catalogue the range of definitions used for key determinants of PAB (steps 1–2). A two-round modified Delphi survey was conducted online from February to September 2023, to determine the optimal definition for each determinant. In round 1, experts selected the most suitable definition for each of the 41 initially identified determinants. In round 2, experts ranked the appropriateness of the definition selected from round 1 on a 5-point Likert scale. Consensus was defined a priori as ≥ 75% agreement on the definition (i.e., ratings of ≥ 4 points). A professional English language expert ensured concise, coherent wording and high-quality editing of the definitions (steps 3–6). Results Eighty-five experts in PAB research participated in round 1, and sixty-nine experts in round 2. Consensus of definitions was achieved for 39 of the 41 determinants (88.4%–98.6% agreement). The consensus threshold was not achieved for two determinants: genetic profile and regulation (69.6%) and backyard access/size (73.9%). Conclusions The findings of this study offer a consensus-based set of definitions for 39 key determinants of PAB. These definitions can be used homogenously in academic research on physical activity.